Kovács, Ágnes Zsófia. The Memory of Architecture in Edith Wharton’s Travel Writing. New York: Routledge, 2025. 212 pp. ISBN 9781032580265 - Vöő, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2025)
This review assesses Ágnes Zsófia Kovács’s The Memory of Architecture, highlighting its revaluation of Edith Wharton’s travel writing as a central component of her oeuvre. It emphasizes Kovács’s argument that Wharton’s travel texts function as forms of historical and cultural inquiry, shaped by an “architectural vision” grounded in visual culture. The review underscores the monograph’s contribution to transnational Wharton studies and its significance within the broader revitalization of Hungarian American Studies.